People management in primary health care: Visions and practices (Research, Society and Development, 2022)
The management of people in primary health care, in addition to developing joint work that includes all the existing human resources in that place, seeks to organize visions which may involve protection, promotion, diagnosis, among other intervention factors, promoting comprehensive care in health care in practice. In this context, the aforementioned work has the general objective of understanding the views and practices of people management in primary health care. Thus, the methodology used corresponded to the integrative review method in order to promote the inclusion of authors who research on people management in primary health care, with works published from 2019 to 2022 on digital scientific platforms. Thus, analyzing what the authors listed on the subject, it was observed the positive points regarding the management of people linked to the field of primary health care as a way to streamline, innovate and enhance practical visions which can provide better results in activities that may be consistent with the local reality, and with that, people management needs to seek ways to motivate health professionals so that the team works to maintain patient safety, in addition to providing quality services. Through what was described throughout the article, it was concluded that people management provides guidance in primary health care in the creation of practical visions which can bring organizational changes, in addition to improving new intervention techniques in the health area.